APLIKASI PROBIOTIK IKAN FISH PRO DALAM KEGIATAN BUDIDAYA IKAN LELE SISTEM BIOFLOK: INDUKSI PAKAN BERPROTEIN RENDAH DAN TINGGI - Maharani, Salsabila Dewi; Wahyuni, Ananda; Junaedi, Abdus Salam; Triajie, Haryo; Zainuri, Muhammad (Universitas Airlangga, 2025)
Catfish farming with the biofloc system is increasingly used because it can increase feed efficiency. However, the main challenge in this system is optimal water quality, especially in relation to the presence of pathogenic bacteria such as coliform. This study aims to determine the effect of giving probiotics to feed with high, low, and control protein content on water quality, water and intestinal TPC, and the level of coliform bacteria in the anus of catfish. The method used in this study is experimental in the laboratory of Trunojoyo Madura University. This research was carried out using 3 treatments, namely control, low, and high protein feed. Data related to the results of measuring water quality parameters pH, temperature are presented in the form of a graph. The results data for detecting pathogenic bacteria in sangkuriang catfish (Clarias gariepinus) were analyzed qualitatively by calculating the Total Plate Count (TPC) value of heterotrophic bacteria growing in Nutrient Agar (NA) media and pathogenic bacteria growing in Eosin Methylene Blue Agar (EMBA). The results of this study are expected to provide a better understanding of how the use of probiotics affects. Temperature values ​​ranged from 26.71-28.83°C, and pH ranged from 8.34-9.45. Bacterial TPC values ​​ranged from 8.03 to 16.94 CFU/ml. The TC value of bacteria in catfish anus samples ranged from 3.81-7.00 CFU/ml. This study can be a practical solution for farmers to improve sustainable catfish cultivation